2016
DOI: 10.3389/fncel.2016.00218
|View full text |Cite
|
Sign up to set email alerts
|

The Endosome Localized Arf-GAP AGAP1 Modulates Dendritic Spine Morphology Downstream of the Neurodevelopmental Disorder Factor Dysbindin

Abstract: AGAP1 is an Arf1 GTPase activating protein that interacts with the vesicle-associated protein complexes adaptor protein 3 (AP-3) and Biogenesis of Lysosome Related Organelles Complex-1 (BLOC-1). Overexpression of AGAP1 in non-neuronal cells results in an accumulation of endosomal cargoes, which suggests a role in endosome-dependent traffic. In addition, AGAP1 is a candidate susceptibility gene for two neurodevelopmental disorders, autism spectrum disorder (ASD) and schizophrenia (SZ); yet its localization and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 60 publications
0
19
0
1
Order By: Relevance
“…For instance, cg10984962; the third-ranking CpG from the meta-analysis, is located in AGAP1 , which encodes a protein involved in endosomal trafficking. In neuronal cells, it plays a role in the recycling of muscarinic acetylcholine receptors(62) and was shown to influence dendritic spine morphology(63). Yet, methylation levels in blood did not correlate with methylation levels in the brain at this CpG.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, cg10984962; the third-ranking CpG from the meta-analysis, is located in AGAP1 , which encodes a protein involved in endosomal trafficking. In neuronal cells, it plays a role in the recycling of muscarinic acetylcholine receptors(62) and was shown to influence dendritic spine morphology(63). Yet, methylation levels in blood did not correlate with methylation levels in the brain at this CpG.…”
Section: Discussionmentioning
confidence: 99%
“…AGAP1 is a regulator of endosomal trafficking and AGAP1 expression levels have been shown to inversely modulate dendritic spine density in hippocampal neuron cultures, suggesting that AGAP1 activity is highly regulated to ensure correct development and maturation of dendritic spines during development. 31 We knocked down expression of AGAP1 in zebrafish larvae and assessed gross morphology at 24 hour post fertilisation (hpf), 48 hpf and 72 hpf and motility and responses to light and tapping stimuli at 96 hpf. Morphant zebrafish larvae showed a range of dosage-dependent, early developmental phenotypes, including generalised developmental delay and convergence extension defects with necrotic tissue in the brain at 24 hpf (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both overexpression and downregulation of AGAP1 have been shown to affect neuronal endosomal trafficking and dendritic spine morphology in mouse primary neurons. 31 Rare variants in AGAP1 have also been previously implicated in autism 48 and suggested as a risk factor for schizophrenia. 31 We demonstrated that AGAP1 morphant zebrafish have reduced startle and escape responses, reduced motility and developmental delay, further supporting a role for AGAP1 in neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…19 AGAP1 was found to affect dendritic spine morphology and endosomal traffic in neurones. 2 This gene also mediates dopamine release through an interaction with M5 muscarinic acetylcholine receptor. 6 These findings suggest that the differential methylation of genes is important for the development and maintenance of neurons and the nervous system and may be an important factor in the development of CWP.…”
Section: Discussionmentioning
confidence: 99%